The Role of Risk Factors (Onset - Hospitalization, Onset - Surgery, Increase in Pulse, Systolic Blood Pressure) on Death in Gastric Perforation - Faisal Amri Lubis; Sarup Singh (Sriwijaya Journal of Surgery, 2019)
ABSTRACT Introduction. Gastric perforation is the second most common complication due to peptic ulcer after bleeding where the risk of mortality in patients who have received surgical treatment is still high. The factors that have the greatest influence on the death of the patient are old age and the time span of handling more than 24 hours. This study aims to determine the relationship between risk factors (onset - hospitalization, onset - surgery, increased pulse, decreased systolic blood pressure) on the death of gastric perforation patients undergoing surgery at Dr. General Hospital Mohammad Hoesin Palembang. Methods: An observational analytic study with a case-control study design was carried out from August to October 2017 at the Dr. General Central Hospital Mohammad Hoesin (RSMH) Palembang. There were 90 respondents consisting of 30 sample groups with death cases and 60 sample groups with life control. The relationship between independent and dependent variables was analyzed by Chi Square test while risk factors that play a role in death in gastric perforation patients who performed surgery were analyzed with the Logistic Regression test. Data analysis uses SPSS version 18.0. Results. There was a significant relationship between increased pulse (OR = 11,227 CI95% 3,923-32,129; p = 0,000), onset - MRS (hospital admission) (OR = 4,125 CI95% 1,579-10,773; p = 0,006) and onset - surgery (OR = 3,786 CI95% 1,267-11,308; p = 0.029) on the death of a gastric perforation patient undergoing surgery. With the Logistic Regression test, an increase in pulse and onset - hospital admission was significantly related to the death of a gastric perforation patient undergoing surgery. Conclusion. It can be concluded that the increase in pulse and onset of hospital admission are risk factors that contribute to the death of gastric perforation patients who undergo surgery.